2012
DOI: 10.1136/bjsports-2011-090688
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of traumatic shoulder injury in elite rugby players

Abstract: BackgroundShoulder injuries in rugby players are common, but the mechanisms of injury are less well understood. This study aims to elucidate common mechanisms of injury and identify the patterns of injury they produce.Materials and methodsTwenty-four elite rugby players, referred to the senior author for diagnosis and management of shoulder injuries, were selected. Videos of the injuries were independently reviewed by rugby-medical experts to describe the mechanisms of injury. The mechanisms reported were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 12 publications
3
80
1
2
Order By: Relevance
“…The injury occurs during are also caused in the tackle. (10) In the present study, this information is highlighted as it was pointed out that the main cause of injury situation is the tackle.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The injury occurs during are also caused in the tackle. (10) In the present study, this information is highlighted as it was pointed out that the main cause of injury situation is the tackle.…”
Section: Methodsmentioning
confidence: 98%
“…Crichton et al (10) in a study with 24 players in the semi professional in a period of four years and revealed that the shoulder was the joint often affected with a prevalence of 7.7%. The analysis of muscle activity patterns and isokinetic strength of semi professional rugby done by Bolton et al (11) showed that shoulder injuries are the most serious in this sport, accounting for almost 20%…”
Section: Resultsmentioning
confidence: 99%
“…The most common mechanisms of shoulder injuries in rugby players were defined by Crichton et al (2012) as the "try-scorer," "tackler," and "direct impact" mechanisms.…”
Section: Injury Prevention In Contact Athletesmentioning
confidence: 99%
“…O tackle é responsável por 50 a 85% das lesões do ombro. Lacerações do manguito rotador, lesões de Bankart, SLAP (Superior Labrum Anterior to Posterior Lesion, ou seja, lesão do lábio superior de anterior para posterior) e luxações são as consequências mais comuns dessa manobra [13,[38][39][40]. Além disso, o MND é o mais atingido porque os atletas protegem-se com esse membro enquanto carregam a bola com o MD [34].…”
Section: /7unclassified